Wolf predation risk and moose movement in eastern Finland - Pusenius, Jyrki; Kukko, Tuomas; Melin, Markus; Laaksonen, Sauli; Kojola, Ilpo (Nordic Board for Wildlife Research, 2020)
Grey wolf Canis lupus is often the main predator of moose Alces alces. Therefore it can be expected that moose are able to recognize the presence of wolves and react to them to avoid predation. We examined the effect of predation risk by wolves on movement patterns by moose in eastern Finland where moose and wolves have co-existed for centuries. The level of wolf predation risk experienced by 20 radio-collared adult moose was classified according to the proportion of their fixes in wolf territories. Our results suggest that moose adjust their movement speed according to the degree they are exposed to the presence of wolves. The adjustment occurred in summer but not in winter. In summer the moose more exposed to wolves moved faster than the moose less exposed to wolves. Season and the structure of the surrounding forests also affected moose movement patterns. Both movement speed and the linearity of movement decreased in winter and with increasing canopy cover. We suggest that by increased moving when exposed to higher risk of predation moose try to keep distance to the predator and/or try to keep themselves spatially and temporally unpredictable to their predator. Our results differ from those obtained in Scandinavia where no response of moose movement to predation risk by wolves has been detected. It might be that wolves’ continuous presence in eastern Finland compared to Scandinavia provide a reason why moose in our study area reacted to the presence of wolves.
Keywords: moose; movement; predation risk; wolf